(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This research paper explores the integration of writing and reading skills in English for Specific Purposes (ESP) education as a means to enhance students’ language proficiency within their specialized fields. Recognizing the importance of effective communication in professional contexts, this study investigates how incorporating reading activities can facilitate the development of writing skills among ESP learners. The paper begins with an overview of ESP’s significance in language teaching, emphasizing the need for tailored instruction that aligns with students’ disciplinary interests and goals.